2014
DOI: 10.1039/c4cp02537g
|View full text |Cite
|
Sign up to set email alerts
|

The dynamic action mechanism of small cationic antimicrobial peptides

Abstract: Antimicrobial peptides form part of the immune system as protection against the action of external pathogens. The differences that exist between mammalian and microbial cell membrane architectures are key aspects of the ability of these peptides to discriminate between pathogens and host cells. Given that the pathogen membrane is the non-specific target of these cationic peptides, different molecular mechanisms have been suggested to describe the rules that permit them to distinguish between pathogens and mamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
45
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(56 citation statements)
references
References 59 publications
11
45
0
Order By: Relevance
“…It is interesting to remark that these experimental results are in line with our model for the mechanisms of action of these compounds proposed on the basis of MD simulations and molecular modeling . On the other hand, our results also clearly show that antibacterial activity within the series is mainly dominated by amino acid residues composition.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…It is interesting to remark that these experimental results are in line with our model for the mechanisms of action of these compounds proposed on the basis of MD simulations and molecular modeling . On the other hand, our results also clearly show that antibacterial activity within the series is mainly dominated by amino acid residues composition.…”
Section: Resultssupporting
confidence: 89%
“…Based on the results obtained from molecular dynamics simulations, we have recently proposed a four‐step molecular mechanism for these small cationic peptides acting as antibacterial agents . Such mechanism includes the following steps: Peptides folding and induction of the phospholipid segregation. Peptides protruding into domains with poor charged phospholipid content. Membrane collapse and pore formation. Peptides transposition and, then, the recovery of the bilayer structure. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been previously observed, both experimentally and theoretically, that the area per lipid is much lower for homogeneous lipid bilayer systems in the absence of any peptide. 42, 43 Experimental studies have suggested an average value of 63.6 Å for the area per lipid of POPC/POPG (7:3) bilayer. 44 Our control simulation in the absence of peptide also shows an average value of 62.74 ± 1.20 Å.…”
Section: Resultsmentioning
confidence: 99%
“…The compressibility modulus of the gel phase ceramide 2 bilayer is reported to be relatively high, k A E 4000 dyne cm À1 , 11,37 which is practically an order of magnitude higher than for phospholipid bilayers in a liquid crystalline phase where k A values are found to be around 100-500 dyne cm À1 . 76,77 The k A values for mixed bilayers as a function of MG or FA concentration in the CER2 bilayer are presented in Fig. 7A and B, respectively.…”
Section: Area Compressibility Modulusmentioning
confidence: 99%